Taxonomic evaluation of misidentification of crude herbal drugs marketed in Iran - Mohammad Reza Joharchi; Mohammad Sadegh Amiri (Mashhad University of Medical Sciences, 2012)
identification, authentication and quality control are essential to ensure safety, therapeutic potency, efficacy and reproducible quality of herbal medicines. The aim of this study is to use taxonomic method for authentication of traditional herbal drugs which are commonly sold in herbal shops in Iran. In this regard, twenty-seven cases of herbal drugs suspected to be adulterated were investigated. Material and Methods: Crude raw material of herbal drugs was prepared from the various markets in Iran and was identified at the Ferdowsi University of Mashhad Herbarium (FUMH). Results: Taxonomic evaluationrevealed that 78 species belonging to 21 families which are traded in Iranian market should be considered asauthentic, adulterated and substituted samples.   Conclusion: It was concluded that nowadays, many of the medicinal plants available in the market have ambiguous identification along with adulteration and contamination. The present study provides awareness amongst the traders, researchers, clinicians and manufacturing units about the ambiguity of authenticity in the traded herbal raw materials.